Industrial training report: Bank Islam Malaysia Berhad / Ameen Azraf Azman - Azman, Ameen Azraf (Universiti Teknologi MARA, Perlis, 2024)
Throughout my internship at Bank Islam Malaysia Berhad (BIMB), I, as an intern, had the chance to gain valuable insights and practical experience in the operations of a prominent Islamic financial institution in Malaysia. This internship aimed to shed light on various aspects of the bank's functioning, providing an in-depth understanding of its commitment to Islamic banking principles, customer service, and efforts to expand in the competitive financial market. The internship offered diverse learning opportunities, enabling me to actively contribute to the bank's daily activities. This hands-on experience provided a practical grasp of how theoretical concepts are applied in a real-world financial setting. A key element of the report is the SWOT analysis conducted on Bank Islam Malaysia Berhad. The analysis focused on identifying the bank's strengths, weaknesses, opportunities, and threats, facilitating a comprehensive assessment of its overall performance. Through this analysis, I gained a more strategic perspective on the bank's position and its potential for growth and improvement. Additionally, the report underscored my personal insights and observations during the internship, enhancing the accuracy and relevance of the findings. Personal experiences offer a unique perspective that complements the data-driven analysis, providing a more holistic understanding of the organization and its operations. In summary, this internship report delivers an insightful and comprehensive overview of my experience at Bank Islam Malaysia Berhad. It highlights significant learning opportunities, contributions, and observations made during the internship, offering valuable information about the bank's dedication to Islamic banking principles, customer service practices, and strategic expansion efforts. The SWOT analysis of BIMB facilitates a strategic evaluation of the bank's position in the dynamic and competitive banking market, guiding informed decision-making and pinpointing potential areas for growth and improvement.